PATTERN OF SEXUAL ASSAULT CASES IN MANIPUR (Journal of Forensic Medicine & Toxicology, 2024)
Sexual assault is an assault of a sexual nature on another person and is regarded as a serious health and human rights problem. The present study was aimed at finding the true pattern of the alleged sexual assault cases which were brought for medicolegal examination to the Forensic Medicine dept of RIMS, Imphal during August 2010-July2012.In this study, the commonest victims were in the age group of 11-20 years (65.29%), & majority of the victims were Meiteis ((79.43%).%). Unmarried victims constituted the majority (92.21%).The maximum numbers of victims were from the rural area (85.82%). Majority of the cases were of elopement (53.90%) and cases of consensual and forcible sexual intercourse accounted for 28.37 % and 17.73% respectively. Maximum number of elopement cases have occurred during the winter (40.79 %) followed by spring season (36.84%). Maximum number of cases of the alleged sexual assaults had occurred in the house of the accused or his relatives (63.83%). Injuries on the body were found on only 8.51% of the victims with 91.49% of them showing no injuries on their body. Old hymeneal tear was seen in 56.73% of the total cases.
Keywords: Sexual assault; victim; assailants; Lover; elopement